Comparing the Tribological Properties of the Coatings (Ti-Hf-Zr-V-Nb-Ta)N and (Ti-Hf-Zr-V-Nb-Ta)N + DLC - U.S. Nyemchenko; V.M. Beresnev; V.F. Gorban; V.Ju. Novikov; O.V. Yaremenko (Журнал нано- та електронної фізики)
The paper compares the tribological characteristics of the coatings (Ti-Hf-Zr-V-Nb-Ta)N and (Ti-Hf-Zr-V-Nb-Ta)N + DLC obtained by means of vacuum-arc deposition method. Coefficients of friction for nitride coatings (Ti-Hf-Zr-V-N-Ta)N have an average value of 1.06; for nitride coatings with DLC the value was 0.5 in the beginning, and then decreased to 0.14. To achieve high performance for functional coatings consisting of two layers - the bottom - and top-nitride DLC it is necessary to ensure the formation of a layer of solid lubricant in the areas of actual contact while retaining the structure of the coating.